Analisis Determinan Pengungkapan Islamic Social Reporting (ISR) (Studi Kasus Pada Perusahaan yang Terdaftar pada Jakarta Islamic Index Tahun 2011 - 2015) - Widiyanti, Novi Wulandari; Hasanah, Nindya Tyas (Universitas Islam Negeri Sunan Kudus, 2017)
This study aims to analyze factors affecting Islamic Social Reporting (ISR) of Jakarta Islamic Index (JII). Islamic Social Reporting (ISR) is a social responsibility disclosure index accordance to the sharia principles. The social responsibility disclosure is accountability to Allah SWT to make a decision for muslim firm report user. ISR was evaluated based on content analysis by analyzing annual report of 55 companies that listed in Jakarta Islamic Index exchange in 2011-2015. There were four factors suspected to influence ISR in this study. The results show that liquidity, profitability and company age significantly affect the disclosure of ISR. Meanwhile, industry type does not affect the disclosure of ISR.